Manajemen Pengembangan Profesionalitas Guru Taman Kanak-kanak - Marzuki Marzuki; Ria Rahayu; Bunga Mercewilly; Hasan Syahrizal (Sekolah Tinggi Teologi Real Batam, 2022)
This study aims to analyze the management of the professional development of kindergarten teachers. Teachers are believed to be one of the dominant factors that determine the success rate of students in carrying out the teaching and learning process in schools which is the spearhead of the implementation of education in the classroom. The approach used in this study is quality with a descriptive type. The subjects in this study were 1 (one) principal who was responsible for the school, and 3 (three) teachers. The object of this study is the management of the professional development of kindergarten teachers. Data collection techniques in the study used observation techniques and in-depth interviews. The data analysis technique in this study used interactive model analysis. The results showed that the principal's management in teacher professional development has been carried out well, where the principal directs these teachers to take part in basic training on early childhood learning which is carried out once a year.Keywords: development; teacher professionalism; managementAbstrakPenelitian ini bertujuan untuk menganalisis manajemen pengembangan profesionalitas guru Taman Kanak-kanak. Guru diyakini sebagai salah satu faktor dominan yang menentukan tingkat keberhasilan peserta didik dalam melakukan proses belajar mengajar di sekolah yang menjadi ujung tombak pelaksanaan pendidikan di kelas. Pendekatan yang digunakan pada penelitian ini adalah kualtitatif dengan jenis desktriptif. Subjek pada penelitian ini adalah 1 (satu) orang kepala sekolah yang bertanggung jawab terhadap sekolah, dan 3 (tiga) orang guru. Objek penelitian ini adalah manajemen pengembangan profesionalitas guru Taman Kanak-kanak. Teknik pengumpulan data dalam penelitian menggunakan teknik observasi dan wawancara mendalam. Teknik analisis data pada penelitian ini menggunakan analisis model interaktif. Hasil penelitian menunjukkan bahwasannya manajemen kepala sekolah dalam pengembangan profesional guru sudah terlaksana dengan baik, dimana kepala sekolah mengarahkan guru-guru tersebut untuk mengikuti diklat dasar mengenai pembelajaran anak usia dini yang di laksanakan setahun sekali.Kata Kunci: pengembangan; profesionalitas guru; manajemen